Quantification of Subjective Scaling of Friction Using a Fingertip Biomechanical Model - Mohammad Abdolvahab (Applied Bionics and Biomechanics)
Subjective scaling of friction is important in many applications in haptic technology. A nonhomogeneous biomechanical finite element model of fingertip is proposed in order to predict neural response of sensitive mechanoreceptors to frictional stimuli (Slowly Adapting SAII receptors under the glabrous skin). In a guided psychophysical experiment, ten human subjects were asked to scale several standard surfaces based on the perception of their frictional properties. Contact forces deployed during the exploratory time of one of the participants were captured in order to estimate required parameters for the model of contact in the simulation procedure. Consequently, the strain energy density at the location of a selective mechanoreceptor in the finite element model as a measure of discharge rate of the neural unit was compared to the subject’s perceptual evaluation of the relevant stimuli. It was observed that the subject’s scores correlate with the discharge rate of the given receptor.